2018
DOI: 10.1002/2017wr021268
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Variability in Public‐Supply Water Use Across the Contiguous United States

Abstract: This study explores the relationship between municipal water use and an array of climate, economic, behavioral, and policy variables across the contiguous U.S. The relationship is explored using Bayesian‐hierarchical regression models for over 2,500 counties, 18 covariates, and three higher‐level grouping variables. Additionally, a second analysis is included for 83 cities where water price and water conservation policy information is available. A hierarchical model using the nine climate regions (product of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 57 publications
(87 reference statements)
4
32
0
Order By: Relevance
“…The effects of mean temperature were also explored, but ultimately eliminated from multiple regression models due to collinearity since mean and maximum temperature were over 99% correlated. Maximum temperature was chosen since it is more prevalent in the literature (Maidment and Miaou 1986;Kenney et al 2008;Worland et al 2018). The best multiple regression model for each city was selected to include a subset of the terms in Equation (A1) based on the corrected Akaike information criterion (AIC c ), a model selection tool used to balance the tradeoff between model fit and simplicity, with a correction for small sample sizes to prevent overfitting.…”
Section: City-specific Regression Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of mean temperature were also explored, but ultimately eliminated from multiple regression models due to collinearity since mean and maximum temperature were over 99% correlated. Maximum temperature was chosen since it is more prevalent in the literature (Maidment and Miaou 1986;Kenney et al 2008;Worland et al 2018). The best multiple regression model for each city was selected to include a subset of the terms in Equation (A1) based on the corrected Akaike information criterion (AIC c ), a model selection tool used to balance the tradeoff between model fit and simplicity, with a correction for small sample sizes to prevent overfitting.…”
Section: City-specific Regression Modelsmentioning
confidence: 99%
“…Other factors such as irrigated area, net evapotranspiration (ET), water price, use of in-ground sprinklers, and excess irrigation together explained 45% of the variation in outdoor water use (DeOreo et al 2016). An analysis using U.S. Geological Survey (USGS) county-level water use found that climate region groupings were more explanatory than primary economic activity or urban gradient, and emphasized that predictive capabilities of social and environmental variables differ across climate regions (Worland et al 2018). An analysis using U.S. Geological Survey (USGS) county-level water use found that climate region groupings were more explanatory than primary economic activity or urban gradient, and emphasized that predictive capabilities of social and environmental variables differ across climate regions (Worland et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other works have also examined the drivers of future water withdrawals in general (Worland et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include interactions between IBTs and the Clean Water Act (Schroeder and Woodcock 2011), effects of IBT connectivity on fish biodiversity (Grant et al 2012), and the economic feasibility of IBTs utilizing optimization models, with maximization of net benefits as the objective (Karamouz et al 2010). Other works have also examined the drivers of future water withdrawals in general (Worland et al 2018).…”
Section: Introductionmentioning
confidence: 99%